PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI GOJEK DI KOTA SURABAYA - Haladi, Athira Yasmin; *, Aisyaturrahmi (IAIN Tulungagung, 2018)
Abstract: Business in the field of public transport, especially those communities needed to help with daily activities. With a lot of public transportation offered more diverse in the city of Surabaya so that make transportation services company compete with each other. Gojek is public transportation technology based applications that provide services such as go-riding, go-cars, go-send, go-mart, go-box,and more. In the services provided gojek there are complaints from customers therefore the author makes this article to determine the effect of the quality of services provided gojek in Surabaya on customer satisfaction. Dimensions of the independent variables of research that is tangible, assurance, empathy, reliability, responsiveness, and the dependent variable of customer satisfaction research.Based on the results showed that the quality of service (tangible, reliability, responsiveness, assurance, and empathy) has positive influence onÂ customer satisfaction by 42.4%, while 57.6% is influenced by othervariables not examined by the researcher.